###### The problem

$y\hspace{0.17em}=\hspace{0.17em}mx+\hspace{0.17em}c,makexasthesubject$

Loading...

For over 5 years, we pride ourselves on our commitment to excellence, as well as our ability to deliver for our customers.

$y\hspace{0.17em}=\hspace{0.17em}mx+\hspace{0.17em}c,makexasthesubject$

$Solution:\phantom{\rule{0ex}{0ex}}y=\hspace{0.17em}mx+c\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}$

$\Rightarrow y-c=mx(takingctotheotherside)$

$\Rightarrow \frac{y-c}{m}=\hspace{0.17em}\frac{mx}{m}(dividingbymonbothsides)\phantom{\rule{0ex}{0ex}}$

$\Rightarrow \frac{y-c}{m}=\hspace{0.17em}x.$